The social cognition of human rights.[article]. - Conaco, Ma. Cecilia Gastardo
This study re-analyzes the Philippine data of a 35-country survey research on the social representations of human rights. In the paper, acceptance and willingness to do something to ensure the upholding of the thirty articles of the universal human rights declaration were related to various personal experiences. These included political participation and involvement, awareness of Philippine social political realities, perception of inter-group tensions, and experiences of personal and social injustice. Differentials among the three respondent categories, social science majors, science majors, and police cadets indicate links between human rights-related social cognitions and one's personal, social and political experiences.